PENERAPAN PEMBELAJARAN BERBASIS DEMONSTRASI DALAM MENINGKATKAN PEMAHAMAN FIQIH SISWA KELAS III DI MI MUHAMMADIYAH BAMBAN GIRIWOYO - Siti Ainun Nafisah; Mukminin, Amir (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
The purpose of this study was to analyze the application of endocrine learning methods in the Fiqh curriculum in class III of MI Muhammadiyah Bamban Giriwoyo and to examine the effectiveness of the method in improving students' understanding and abilities in the Fiqh subject. The Fiqh curriculum in class III of MI Muhammadiyah Bamban Giriwoyo and to examine the effectiveness of the method in improving students' understanding and abilities in the subject of qualitative approach with a case study design based on descriptive-analytical theory. The purpose of this method is to find out in detail the application of the conservation method in the fiqh education program at MI Muhammadiyah Bamban Giriwoyo. Data collection techniques with three stages. First, participatory observation which includes direct observation of the learning process, documentation of freezing activities and systematic field recording. Second, in-depth interviews include semi-structured interviews, focusing on teacher experience and student perceptions and friangulation of information sources. Third, documentation. Resonance-based learning at MI Muhammadiyah Bamban Giriwoyo in the fiqh subject is considered capable and very effective for learning. The research sample included Islamic religious education teachers and students of class III of MI Muhammadiyah Bamban Giriwoyo. The results of the study showed that implementing learning using the condensation method was very effective in improving student understanding.